2015
DOI: 10.1007/s00192-014-2619-z
|View full text |Cite
|
Sign up to set email alerts
|

Creating a gold standard surgical procedure: the development and implementation of TVT

Abstract: The last two decades have witnessed a launch of new surgical procedures, utilizing kits and synthetic materials, at a pace not formerly seen. Some launches have been preceded by thorough clinical documentation and others not. Any innovation, be it a theory or a treatment concept, is only fantasy until it has been tested and clinically documented.Within the field of surgical management of female stress urinary incontinence the presentation of the mid-urethral theory (a part of the integral theory [1]) implied a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The most common complication at retropubic approach is urinary retention (17%–50%). [ 24 29 ] In de Tayrac's study,[ 49 ] urinary retention was reported in 13.3% of women after TOT and 25.8% of women after TVT. Similar to that, urinary retention in our study was present in 10,0% of women after TOT procedure, 10.1% after SIMS and at 13.7%of women after TVT procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common complication at retropubic approach is urinary retention (17%–50%). [ 24 29 ] In de Tayrac's study,[ 49 ] urinary retention was reported in 13.3% of women after TOT and 25.8% of women after TVT. Similar to that, urinary retention in our study was present in 10,0% of women after TOT procedure, 10.1% after SIMS and at 13.7%of women after TVT procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Standard operating techniques were used as described by Petros and Papadimitriou,[ 13 ] Ulmsten,[ 29 ] and Delorme. [ 30 31 ] The surgeons involved in this study had experience with all surgical the abovementioned techniques.…”
Section: P Atients and M Ethodsmentioning
confidence: 99%
“…He published more than 100 scientific papers and was supervisor for six theses. He was extremely involved both nationally and internationally in numerous organizations, especially within the urogynecology profession, including the International Urogynecological Association (IUGA) [2], and a member of the executive committee of the European Urogynaecological Association (EUGA) until his death, chairman of the Finnish Society of Medicine 2008-2009, and became an honorary member of the Finnish Gynaecological Society in 2009. Although he formally retired in 2012, he remained highly participatory in the assessment of modern surgical techniques within urogynecology.…”
mentioning
confidence: 99%
“…The term Bgold standard^is used quite often in medicine [1,2]. It says that there is a standard that clinicians should follow and that this is the best standard available, backed by solid evidence and broad consensus.…”
mentioning
confidence: 99%